Corporate growth, age and ownership structure: empirical evidence in Spanish firms - Moreno, Justo de Jorge; Castillo, Leopoldo Laborda (Journal of Business Economics and Management, 2011)
The objective of this work is to analyse firm mobility among the different sectors of the Spanish economy according to a statistical classification of economic activities at the 1-digit level. Some of the stylised facts that we find are: an inverse relation between firm growth and age; an increase in new entrants’ average relative size in terms of sales compared to established firms among the different industries and cohorts; the importance of the firm's initial size in entrepreneurial activity; the favourable impact of the economy on firm growth; and a positive relation between non-concentration in the ownership structure and greater mobility. In this context, an efficient corporate governance system may prove as a significant policy tool for the investment and growth prospective of the Spanish economy. The regulatory framework of the Spaniard capital market has been coordinate with the EU standards. The challenge is now mostly for the firms to adopt the appropriate corporate governance structures, in order to achieve real convergence, in terms of productivity and competitiveness, with other developed economies.Article in English.Kompanijos dydis, amžius ir nuosavybės struktūra: empirinis tyrimas Ispanijos įmonėse Santrauka. Pateikiami empirinio tyrimo, atlikto Ispanijos kompanijose, rezultatai. Tirti buvo pasirinktos skirtingiems pramones sektoriams (pagal ekonomikos veiklu klasifikatoriu) priklausanèios imones. Tyrimo metu nustatyta, kad egzistuoja sryšis tarp imones dydžio ir amžiaus, kad itakos turi ir skirtingi pramones sektoriai, kuriuose veikia imone, nustatytas sryšis tarp imones dydžio bei ekonominio aktyvumo, imones nuosavybes ir augimo. Atsižvelgiant i tai, siuloma veiksminga verslo valdymo sistema, kuri gali buti priimta kaip viena svarbiausiu politikos priemoniu pritraukiant investicijas ir didinant Ispanijos ekonomikos augim. Pasiulytosios veiksmingos verslo valdymo sistemos priemones pades imonems didinti produktyvum ir stiprinti konkurencini pranašum, palyginti su kitomis ekonomiškai stipriomis valstybemis.Reikšminiai žodžiai: imones dydis, imones amžius, ekonominis augimas, nuosavybes forma, Ispanijos imones.